Glue for Manufacturing Heel Prick Filter Cards Does Not Interfere with the Measurement of Analytes for Newborn Screening - Rose E. Maase; Marelle J. Bouva; Peter C. J. I. Schielen (MDPI AG, 2017)
Population-based newborn screening (NBS) using blood collected and dried on filter paper was developed in the 1960s and remains the international standard for NBS programs. Glue, used in the manufacture of dried blood collection cards, may present a source of contamination and is often considered as a possible cause of anomalous results in routine screening. Our study evaluates this potential contamination on NBS analyses. EBF#1003 glue was blotted onto dried blood collection cards made of Whatman grade 903 filter paper (Whatman#903) and adult whole blood was pipetted onto the dried glue blots. In addition, blank glue blots (i.e., no blood) and dried blood spots (DBSs) in the absence of glue were prepared. The DBSs and blank samples were run in duplicate as routine samples for NBS. DBS absorption time and diameter, the effect of glue on measurements (concentrations and variation) were assessed. DBS absorption time and shape were equivalent for DBSs prepared in the absence and presence of undiluted glue. DBS diameter increased when prepared in the presence of glue. When EBF#1003 was diluted prior to use, DBS absorption time increased, and DBSs were non-uniform. Glue, diluted or not, did not produce measurements above the established Limit of Detection (LOD) for all assays used in the current Dutch screening programme. For all analytes with concentrations in the quantifiable range, contamination with glue had no effect on measurement variation, as it appeared equivalent to variation in untreated DBSs. Our data show that, in the unlikely event of contamination of Whatman#903 with EBF#1003, there is no effect on the measured concentration of analytes.